2021
DOI: 10.1371/journal.pone.0250720
|View full text |Cite
|
Sign up to set email alerts
|

Effects of juvenile hormone in fertility and fertility-signaling in workers of the common wasp Vespula vulgaris

Abstract: In the highly eusocial wasp, Vespula vulgaris, queens produce honest signals to alert their subordinate workers of their fertility status, and therefore they are reproductively suppressed and help in the colony. The honesty of the queen signals is likely maintained due to hormonal regulation, which affects fertility and fertility cue expression. Here, we tested if hormonal pleiotropy could support the hypothesis that juvenile hormone controls fertility and fertility signaling in workers. In addition, we aimed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…In social wasps, JH has been shown to influence transitions between worker tasks by accelerating the behavioral ontogeny in experimentally treated individuals (O'Donnell and Jeanne, 1993;Chang et al, 2015;Giray et al, 2005;Shorter and Tibbetts, 2009;Tibbetts et al, 2013). As JH also causes an increase in the oocyte length of workers by acting as an ovarian activator (Kelstrup et al, 2014b;Oi et al, 2021), both reproductive and behavioral traits are controlled by the same endocrine pathway (O'Donnell and Jeanne, 1993;Kelstrup et al, 2014b). Furthermore, JH also appears to be involved in regulating pheromone production, such as the cuticular hydrocarbon (CHC) profiles of queens and workers (Robinson and Vargo, 1997;Oliveira et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In social wasps, JH has been shown to influence transitions between worker tasks by accelerating the behavioral ontogeny in experimentally treated individuals (O'Donnell and Jeanne, 1993;Chang et al, 2015;Giray et al, 2005;Shorter and Tibbetts, 2009;Tibbetts et al, 2013). As JH also causes an increase in the oocyte length of workers by acting as an ovarian activator (Kelstrup et al, 2014b;Oi et al, 2021), both reproductive and behavioral traits are controlled by the same endocrine pathway (O'Donnell and Jeanne, 1993;Kelstrup et al, 2014b). Furthermore, JH also appears to be involved in regulating pheromone production, such as the cuticular hydrocarbon (CHC) profiles of queens and workers (Robinson and Vargo, 1997;Oliveira et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the oocyte size was increased after treatment with the methoprene; nevertheless, oocyte size was decreased against precocene. Thus, JH affects both fertility and fertility signaling in workers [66].…”
Section: Juvenile Hormone Regulated Reproduction In Insectsmentioning
confidence: 99%
“…In swarm-founding species, JH has been reported to control behavioral maturation in Polybia occidentalis (Prato et al, 2021), and ovary activation and chemical expression of CHCs in P. occidentalis (Prato et al, 2021) and Synoeca surinama (Kelstrup et al, 2014). In highly eusocial wasps, JH effects have been well studied so far in a single species, namely Vespula vulgaris, and one of the roles is being associated with regulating reproductive traits in females, leading to modification of certain cuticular compounds over the cuticle (Oliveira et al, 2017;Oi et al, 2020Oi et al, , 2021a. By treating workers topically with a JH analog (methoprene), studies in the past have supported that in addition to the regulation of CHC production, JH may be directly responsible for increasing the proportion of queen pheromones in V. vulgaris (the compounds n-C27, n-C28, n-C29, and 3-MeC29) (Oliveira et al, 2017;Oi et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…In highly eusocial wasps, JH effects have been well studied so far in a single species, namely Vespula vulgaris, and one of the roles is being associated with regulating reproductive traits in females, leading to modification of certain cuticular compounds over the cuticle (Oliveira et al, 2017;Oi et al, 2020Oi et al, , 2021a. By treating workers topically with a JH analog (methoprene), studies in the past have supported that in addition to the regulation of CHC production, JH may be directly responsible for increasing the proportion of queen pheromones in V. vulgaris (the compounds n-C27, n-C28, n-C29, and 3-MeC29) (Oliveira et al, 2017;Oi et al, 2021a). Furthermore, in V. vulgaris, increasing JH levels may be decisive for reproductive workers to succeed (Oi et al, 2020), as workers treated with methoprene lay eggs that chemically resemble those laid by queens, and in doing so, their eggs were less policed (Oi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation